Apocalyptic and the New Testament essays in honor of J. Louis Martyn - Marcus, Joel; Soards, Marion L. (Sheffield JSOT, 1989)
Includes bibliographical references and indexes.
Keywords: Martyn, J. Louis; Bible. N.T. -- eschatology